Growth and yield of rice fields with posbidik compost and jajar legowo planting system - I Ketut Suweta; Hertasning Yatim; Mihwan Sataral (CELEBES Agricultural, 2021)
Posbidik compost is an innovative product that is expected to solve the scarcity of subsidized fertilizers for farmers. The principle of the jajar legowo planting system is to increase plant population and lowland rice production. This study aimed to determine the influence of posbidik compost and jajar legowo planting system on the growth and yield of Ciherang rice varieties. This study was conducted on irrigation paddy fields owned by farmers in West Toili District, Banggai Regency, in August-December 2020. This study used a factorial randomized block design consisting of 2 factors, namely posbidik compost consisting of 3 levels, namely: K1 = 5 tons/ha; K2 = 7.5 tons/ha; K3 = 10 tons / ha, and planting system legowo 2:1 line consisting of 3 levels, namely: L1 = 20 x 10 x 40 cm; L2 = 25 x 12.5 x 50 cm; L3 = 30 x 15 x 60 cm. The results showed that the interaction of posbidik compost and jajar legowo planting system does not affect the plant height; however, it affects the number of productive tillers, the weight of 1000 grains and productivity. The results showed that the best performance of the yield rice in the treatments of 7.5 tons/ha posbidik dose with planting space of 25 x 12.5 x 50 cm.